2022
DOI: 10.3390/cancers14225634
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between PD-L1 Expression of Non-Small Cell Lung Cancer and Data from IVIM-DWI Acquired during Magnetic Resonance of the Thorax: Preliminary Results

Abstract: This study aims to investigate the correlation between intravoxel incoherent motion diffusion-weighted imaging (IVIM-DWI) parameters in magnetic resonance imaging (MRI) and programmed death-ligand 1 (PD-L1) expression in non-small cell lung cancer (NSCLC). Twenty-one patients diagnosed with stage III NSCLC from April 2021 to April 2022 were included. The tumors were distinguished into two groups: no PD-L1 expression (<1%), and positive PD-L1 expression (≥1%). Conventional MRI and IVIM-DWI sequences were acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The D * value in this study was not only identified as one of the independent predictors of PFS but also showed an inverse trend with the risk of progression of NSCLC. This may be related to the fact that lesions with poorer prognoses tend to be more malignant, have tortuous vascular pathways, and thus have reduced average blood velocity 29 . However, some studies concluded that D * was not effective in assessing the prognosis of patients with NSCLC 27,30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The D * value in this study was not only identified as one of the independent predictors of PFS but also showed an inverse trend with the risk of progression of NSCLC. This may be related to the fact that lesions with poorer prognoses tend to be more malignant, have tortuous vascular pathways, and thus have reduced average blood velocity 29 . However, some studies concluded that D * was not effective in assessing the prognosis of patients with NSCLC 27,30 .…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to the fact that lesions with poorer prognoses tend to be more malignant, have tortuous vascular pathways, and thus have reduced average blood velocity. 29 However, some studies concluded that D* was not effective in assessing the prognosis of patients with NSCLC. 27,30 One possible explanation for these varying findings is that different types of treatments may significantly affect the outcome of perfusion-related parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The application of multiparametric magnetic resonance imaging (MRI) to lung cancer analysis is a thoroughly explored field since MRI provides better tissue characterization compared to computed tomography (CT) while involving no exposure to ionizing radiation [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%